Ob 5. obletnici izhajanja revije Acta medico–biotechnica / On the 5th anniversary of Acta medico–biotechnica - Pahor, Dušica (Acta Medico-Biotechnica, 2022)
Dear readers,In front of you is the 10th issue of Acta medico–biotechnica. Founded by the Faculty of Medicine of the University of Maribor as a scientific–research journal in the field of medicine and biotechnics, the first issue of Acta medico–biotechnica was published on December 3, 2008. Acta medico– biotechnica is thus the first scientific journal published by a Faculty of Medicine in Slovenia. The journal is intended for asserting and broadening the scientific findings in the area of medicine and biotechnics, with emphasis on an interdisciplinary approach. Its purpose is to bridge clinical and research work. As a part of the international European community, the journal is published twice a year in Slovene and English. The response of researchers in the field of medicine and biotechnic science has been remarkable. To date, 85 articles have been published, including 45 original and 13 scientific review articles.